High frequency microseismic noise as possible earthquake precursor (Research in Geophysics, 2013)
Before an earthquake occurs, microseismic noise in high frequency (HF) range, i.e. 2-25 Hz, is being generated during preparation process. These signals change the microseismic noise and, consequently, the spectrum of microseismic noise. Time variation of spectra recorded at the same seismological station could imply the change of the state of noise source. We propose the image moment analysis approach to objectively compare microseismic noise spectra. The result could be used for earthquake precursor identification. Expected spectra change is in HF range, so the analysis has been limited to the shallow tectonic earthquakes with epicenters close, up to 15 km, the seismological stations. The method has been tested post festum using four earthquakes in Dinarides which satisfied condition for epicentral distance. The spectra were calculated for noise recorded in time intervals of 10 days before and 6 to 10 days after the earthquakes. Affine moment invariants were calculated for noise spectra which were treated as the input objects. Spectra of the first five days in the series were referent spectra. The classification parameters were Euclidean distances between referent spectra and the spectra for all days in the series, including referent ones. The results have shown that the spectra of the microseismic noise become noticeably different than the other spectra in time intervals one or two days before an earthquake.